Differential Response in Regenerated Shoot Number (Coppicing Ability) of Sixty Clones of Eucalyptus tereticornis Sm. Following Hedging in VMG - Verma, S. K.; Sharma, V. K.; Bagchi, S. K.; Ginwal, H. S. (Indian Forester, 2003)
This paper summarizes the results of differential response in sprouting behaviour of sixty clones after pruning in Eucalyptus tereticornis in Vegetative Multiplication Garden (VMG). The maximum number of shoots 15.2 was observed in clone 5(A) followed by 14.6 and 14.5 in clone 7210320 and 82102051 respectively. Highly significant (P<0.05) correlations werc observed between number of shoots and collar diameter. It was observed that with the increase in diameter of the coppiced stump, the number of shoots produced per stump increased significantly. It was concluded that by pruning of Eucalyptus tereticornis ramets, maximum number of shoots cuttings may be made available from a hedge-garden to produce rooted cuttings on a mass scale for clonal forestry programme by judicious selection of clones having high regenerating capacity of shoot production following hedging.